Pijat Oksitosin sebagai Upaya Meningkatkan Produksi ASI di RS Ken Saras - Dwiyanti, Feni; Mila Elvi Ekayanti; Putri Cahya; Ida Sofiyanti; Yulia Nur Khayati; Rini Susanti; Siti Musarofah (Universitas Ngudi Waluyo, 2024)
Exclusive breastfeeding for the first 6 months of a baby's life is crucial, yet many mothers still experience challenges with inadequate milk production. Oxytocin massage is one solution to increase breast milk production by stimulating the oxytocin hormone. This community service aims to improve postpartum mothers' knowledge and understanding of oxytocin massage as an effort to increase breast milk production.The method used was observation with 20 postpartum mother respondents at Ken Saras Hospital. The activity was conducted in three stages: 1) Assessment of mothers' initial knowledge about oxytocin massage, 2) Socialization and practice of oxytocin massage, 3) Evaluation of mothers' knowledge after the education.Pre-test results showed that mothers' initial knowledge was still lacking, especially regarding the definition, benefits, and techniques of oxytocin massage. Mothers' education and occupation factors influenced their knowledge level. After the education, there was a significant increase in knowledge. The average pre-test score of 50.83 increased to 81.66 in the post-test. Mothers gained a better understanding of oxytocin massage as an effort to increase breast milk production.In conclusion, education and practice of oxytocin massage effectively improved postpartum mothers' knowledge about the benefits and techniques of oxytocin massage for smooth breast milk production. The increase in knowledge is expected to encourage mothers to apply oxytocin massage independently. Recommendations include: 1) Conducting health promotion with village midwives and local health centers, 2) Providing education and training on oxytocin massage to posyandu cadres, 3) Conducting ongoing mentoring for postpartum mothers. With these efforts, it is hoped that exclusive breastfeeding coverage can be increased through optimization of mothers' breast milk production using the oxytocin massage method.. Abstrak Pemberian ASI eksklusif selama 6 bulan pertama kehidupan bayi sangat penting, namun masih banyak ibu yang mengalami kendala produksi ASI yang tidak lancar. Pijat oksitosin merupakan salah satu solusi untuk meningkatkan produksi ASI dengan merangsang hormon oksitosin. Pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan dan pemahaman ibu nifas tentang pijat oksitosin sebagai upaya meningkatkan produksi ASI.Metode yang digunakan adalah observasi dengan 20 responden ibu nifas di RS Ken Saras. Kegiatan dilakukan dalam tiga tahap: 1) Kajian pengetahuan awal ibu tentang pijat oksitosin, 2) Sosialisasi dan praktik pijat oksitosin, 3) Evaluasi pengetahuan ibu setelah penyuluhan. Hasil pre-test menunjukkan pengetahuan awal ibu masih kurang, terutama terkait pengertian, manfaat, dan teknik pijat oksitosin. Faktor pendidikan dan pekerjaan ibu berpengaruh terhadap tingkat pengetahuan. Setelah diberikan penyuluhan, terjadi peningkatan pengetahuan yang signifikan. Nilai rata-rata pre-test 50,83 meningkat menjadi 81,66 pada post-test. Ibu menjadi lebih memahami tentang pijat oksitosin sebagai upaya meningkatkan produksi ASI.Kesimpulannya, penyuluhan dan praktik pijat oksitosin efektif meningkatkan pengetahuan ibu nifas tentang manfaat dan teknik pijat oksitosin untuk kelancaran produksi ASI. Peningkatan pengetahuan diharapkan dapat mendorong ibu untuk menerapkan pijat oksitosin secara mandiri. Saran yang diberikan antara lain: 1) Melakukan promosi kesehatan bersama bidan desa dan puskesmas setempat, 2) Memberikan penyuluhan dan pelatihan pijat oksitosin kepada kader posyandu, 3) Melakukan pendampingan berkelanjutan pada ibu nifas. Dengan upaya tersebut, diharapkan cakupan ASI eksklusif dapat meningkat melalui optimalisasi produksi ASI ibu dengan metode pijat oksitosin.